Characteristics of myosin profile in human vastus lateralis muscle in relation to training background - Zawadowska, B.; Majerczak, J.; Semik, D.; Karasinski, J.; Kolodziejski, L.; Kilarski, W. M.; Duda, K.; Zoladz, J. A. (Folia Histochemica et Cytobiologica, 2004)
Twenty-four male volunteers (mean +/- SD: age 25.4+/-5.8 years, height 178.6+/-5.5 cm, body mass 72.1+/-7.7 kg) of different training background were investigated and classified into three groups according to their physical activity and sport discipline: untrained students (group A), national and sub-national level endurance athletes (group B, 7.8+/-2.9 years of specialised training) and sprint-power athletes (group C, 12.8+/-8.7 years of specialised training). Muscle biopsies of vastus lateralis were analysed histochemically for mATPase and SDH activities, immunohistochemically for fast and slow myosin, and electrophoretically followed by Western immunoblotting for myosin heavy chain (MyHC) composition. Significant differences (P<0.05) regarding composition of muscle fibre types and myosin heavy chains were found only between groups A (41.7+/-1.6% of MyHCI, 40.8+/-4.0% of MyHCIIA and 17.5+/-4.0% of MyHCIIX) and B (64.3+/-0.8% of MyHCI, 34.0+/-1.4% of MyHCIIA and 1.7+/-1.4% of MyHCIIX) and groups A and C (59.6+/-1.6% of MyHCI, 37.2+/-1.3% of MyHCIIA and 3.2+/-1.3% of MyHCIIX). Unexpectedly, endurance athletes (group B) such as long-distance runners, cyclists and cross country skiers, did not differ from the athletes representing short term, high power output sports (group C) such as ice hockey, karate, ski-jumping, volleyball, soccer and modern dance. Furthermore, the relative amount of the fastest MyHCIIX isoform in vastus lateralis muscle was significantly lower in the athletes from group C than in students (group A). We conclude that the myosin profile in the athletes belonging to group C was unfavourable for their sport disciplines. This could be the reason why those athletes did not reach international level despite of several years of training.